The distribution of epigenetic histone marks differs between the X and Y chromosomes in Silene latifolia - Bačovský, Václav; Houben, Andreas; Kumke, Katrin; Hobza, Roman (Planta, 2019)
Contrasting patterns of histone modifications between the X and Y chromosome in Silene latifolia show euchromatic histone mark depletion on the Y chromosome and indicate hyperactivation of one X chromosome in females. Silene latifolia (white campion) is a dioecious plant with heteromorphic sex chromosomes (24, XX in females and 24, XY in males), and a genetically degenerated Y chromosome that is 1.4 times larger than the X chromosome. Although the two sex chromosomes differ in their DNA content, information about epigenetic histone marks and evidence of their function are scarce. We performed immunolabeling experiments using antibodies specific for active and suppressive histone modifications as well as pericentromere-specific histone modifications. We show that the Y chromosome is partially depleted of histone modifications important for transcriptionally active chromatin, and carries these marks only in the pseudo-autosomal region, but that it is not enriched for suppressive and pericentromere histone marks. We also show that two of the active marks are specifically enriched in one of the X chromosomes in females and in the X chromosome in males. Our data support recent findings that genetic imprinting mediates dosage compensation of sex chromosomes in S. latifolia.
Keywords: Sex chromosomes; histonový kód; chromozomy rostlin; Silene; Chromosomes, Plant; Pseudo-autosomal region; epigeneze genetická; Histone Code; Posttranslational histone modifications; Epigenesis, Genetic